Perspective of the nursing staff at hospitals affiliated to the Tehran University of Medical Sciences on the roles and activities of the nurses - S Zokaie Yazdi; J Mosayyeb Moradi; A Mehran (Tehran University of Medical Sciences, 2002)
Nurses play various roles and have various responsibilities in helping patients or other members of the society for example in training, providing support, caring, and in coordinating. The proper performance of these services is dependent on their undertaking of these various responsibilities. Nurses with increased knowledge as to their responsibilities and the proper fulfilling of these in the various fields can be influential in the success of treatment measures. This research is a descriptive study to assess the nursing staff's perception of their roles and activities at hospitals affiliated to the Tehran University of Medical Sciences, conducted on a random sampling in the years of 2001 -2002. Some 104 male and female members of the nursing staff, randomly chosen, participated in this research. The data was collected by means of some questionnaires of 3 parts containing 8 questions related to demographic characteristics, 41 questions related to the quadric roles namely, teaching, supporting, protecting, coordinating, and 2 open questions regarding obstacles and their suggestions in preventing these obstacles. Analysis of data has been done by using SPSS descriptive and inferential statistics. The results with respect to the roles of nurses in different fields show that most of their roles were in teaching activities in relation to patients, in support relating to stressful and upset patients, in the field of protection during catheterizing and dressing and coordinating daily visits. Results relating to the level of performance of these responsibilities are as follows 31.7% in training activities, 35.6% supporting activities, 38.45% protection and 54.8% coordinating activities, respectively, stood at a favorable level. The greatest percentage of unfavorable performance was noted in the supporting role of the nurses. The results also showed that the level of readiness of the nurses to perform the above mentioned four roles was registered as average to good. In addition some factors such as frustration, lack of on the job training, insufficient number of personnel, lack of proper facilities, and insufficient income..., have a great impact on nurses and the removal of obstacles in the performance of their duties.